Gene therapy ameliorates spontaneous seizures associated with cortical neuron loss in a Cln2R207X mouse model - Keigo Takahashi; Elizabeth M. Eultgen; Sophie H. Wang; Nicholas R. Rensing; Hemanth R. Nelvagal; Joshua T. Dearborn; Olivier Danos; Nicholas Buss; Mark S. Sands; Michael Wong; Jonathan D. Cooper (The Journal of Clinical Investigation, 2023)
Although a disease-modifying therapy for classic late infantile neuronal ceroid lipofuscinosis (CLN2 disease) exists, poor understanding of cellular pathophysiology has hampered the development of more effective and persistent therapies. Here, we investigated the nature and progression of neurological and underlying neuropathological changes in Cln2R207X mice, which carry one of the most common pathogenic mutations in human patients but are yet to be fully characterized. Long-term electroencephalography recordings revealed progressive epileptiform abnormalities, including spontaneous seizures, providing a robust, quantifiable, and clinically relevant phenotype. These seizures were accompanied by the loss of multiple cortical neuron populations, including those stained for interneuron markers. Further histological analysis revealed early localized microglial activation months before neuron loss started in the thalamocortical system and spinal cord, which was accompanied by astrogliosis. This pathology was more pronounced and occurred in the cortex before the thalamus or spinal cord and differed markedly from the staging seen in mouse models of other forms of neuronal ceroid lipofuscinosis. Neonatal administration of adeno-associated virus serotype 9–mediated gene therapy ameliorated the seizure and gait phenotypes and prolonged the life span of Cln2R207X mice, attenuating most pathological changes. Our findings highlight the importance of clinically relevant outcome measures for judging preclinical efficacy of therapeutic interventions for CLN2 disease.